Empreendedorismo como alternativa para crise do emprego: avaliação do programa corredores digitais - Castro, Maíra Nobre de (2021)
In the current neoliberal agenda, which is hegemonic in the world order, we have a strong influence of the international financial system. This context has generated crises and caused an increase in social inequalities and unemployment, especially in the State of Ceará. These configurations interfere in the organization of the State, development and entrepreneurship. From this perspective, it was observed in the State of Ceará that, as a public policy for youth, the Digital Corridors Program was forwarded, which, among other purposes, aims at training, mentoring and networking. Carried out by the Department of Science, Technology and Higher Education (SECITECE) for students who aim to transform their ideas, research, inventions or business in pre-operational stage into innovative, competitive, profitable and socially responsible business models. Given these facts, this study aims to assess how the Digital Corridors Program encourages entrepreneurship to help minimize the employment crisis in the State of Ceará. The starting point for the construction of the investigation process of this study was the bibliographical research, from which the theoretical categories-State, Development and Entrepreneurship were formulated, which guided this research. The qualitative perspective as a methodology was guided by an “in-depth assessment”, which we take as a reference for an analytical category the content analysis and the trajectory of the policy. In this evaluation course, we carried out semi-structured interviews with managers linked to SECITECE and we investigated the perception of the program's beneficiaries, in order to investigate the intended effects of combating inequalities through the encouragement of youth entrepreneurship. The deepening in the field, and the relationship between the analytical and theoretical categories showed us that the program, from a conceptual point of view, brings out the figure of the State as an articulator and inductor of entrepreneurship, local development and reduction of inequality, in the however, in its implementation and trajectory, it induces values of competition, individualism and liberalism. By incorporating the proposal of entrepreneurship as an alternative to employment, the policy reproduces excluding values that clash with its initial proposal for the insertion of young people into productive life, emancipation and reduction of inequality. In our perception, we point out the absence of channels that allow for the approximation of a political dialogue between young people and the social and economic context of which they are part.